2012
DOI: 10.1111/j.1099-1123.2012.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Internal Audit Attributes and External Audit's Reliance on Internal Audit: Implications for Audit Fees

Abstract: This study aims to examine two aspects of internal audit quality, namely internal audit competency and internal audit contribution to financial statement audits. Consistent with the substitution view, this study predicts a negative relationship between the competency aspects of internal audit (the tenure of the existence of internal audit in the organization, internal audit staff expertise in IT and computer skills, training hours, internal audit staff professional certifications in accounting and auditing, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 39 publications
7
49
0
Order By: Relevance
“…To be efficient, more autonomous IAFs should, then, either increase co‐sourcing or, alternatively, increase employees' expertise. The results also indicate a negative association between IAF expertise, and in particular IAF internal expertise, and co‐sourcing fees, which is in line with more experienced IAFs being more competent (Mohamed et al, ) and, thus, needing less external support.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…To be efficient, more autonomous IAFs should, then, either increase co‐sourcing or, alternatively, increase employees' expertise. The results also indicate a negative association between IAF expertise, and in particular IAF internal expertise, and co‐sourcing fees, which is in line with more experienced IAFs being more competent (Mohamed et al, ) and, thus, needing less external support.…”
Section: Resultssupporting
confidence: 59%
“…With regard to the tenure of an IAF, Carey et al () found that most of the companies that decided to outsource internal audit activities did not have an in‐house internal department before that decision. Also, Mohamed, Zain, Subramaniam, and Yusoff () found that an increasing IAF tenure leads to more mature and competent IAFs. This result might be interpreted as more experienced IAFs not needing as much support as inexperienced IAFs.…”
Section: Hypotheses Developmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Many studies show that the contribution of the IAF reduces external audit fees. This relationship has already been examined in American (Felix et al, 2001) and Malaysian contexts (Mat Zain et al, 2015;Mohamed et al, 2012). Then, it is interesting to study this relationship in France for several reasons.…”
Section: French Contextmentioning
confidence: 84%
“…Like Pizzini et al (Pizzini, Lin, & Ziegenfuss, 2015), Prawitt et al (2011) andMessier Jr. et al (2011); we use the responses of 2,160 internal auditors to a global survey carried out by the IIA's Global Audit Information Network (GAIN). 1 Unlike Mohamed, Mat Zain, Subramaniam, and Wan Yusoff (2012), assessment of the IAF's contribution to financial reporting quality is based on objective questions such as number of hours worked by IA for external audit or the money spent on the IAF by the organization. In this research, we study the direct effect of the quality of IA and its contribution to the audit of financial statements in the French context.…”
Section: Introductionmentioning
confidence: 99%